2022
DOI: 10.3390/molecules27041306
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Time–Concentration Data Points from Progress Curves Improves the Determination of Km: The Example of Paraoxonase 1

Abstract: Several approaches for determining an enzyme’s kinetic parameter Km (Michaelis constant) from progress curves have been developed in recent decades. In the present article, we compare different approaches on a set of experimental measurements of lactonase activity of paraoxonase 1 (PON1): (1) a differential-equation-based Michaelis–Menten (MM) reaction model in the program Dynafit; (2) an integrated MM rate equation, based on an approximation of the Lambert W function, in the program GraphPad Prism; (3) variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We found that both enantiomers of vutiglabridin significantly and dose-dependently protect against the decrease of rePON1 lactonase activity induced by OX-LA in a manner comparable to glabridin ( Figure 2 B). At 30 μM, under equivalent conditions, the rePON1 lactonase kinetic parameters K m and V max values were evaluated using iFIT program, which enables prompt and precise analysis of enzyme kinetic parameters [ 30 ]. We found that the catalytic efficiency (V max /K m ) was non-significantly increased by vutiglabridin treatment compared to the OX-LA treated group ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that both enantiomers of vutiglabridin significantly and dose-dependently protect against the decrease of rePON1 lactonase activity induced by OX-LA in a manner comparable to glabridin ( Figure 2 B). At 30 μM, under equivalent conditions, the rePON1 lactonase kinetic parameters K m and V max values were evaluated using iFIT program, which enables prompt and precise analysis of enzyme kinetic parameters [ 30 ]. We found that the catalytic efficiency (V max /K m ) was non-significantly increased by vutiglabridin treatment compared to the OX-LA treated group ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…OX-LA was identified to specifically decrease rePON1 activity by oxidizing free sulfhydryl Cys284 and disrupting the protein stability. Glabridin was reported to bind to rePON1 at an allosteric and hydrophobic site that is different from the substrate binding site of the enzyme and modify the protein conformation to decrease the availability of Cys284, therefore protecting rePON1 from OX-LA [ 30 ]. Vutiglabridin and its enantiomers were found to bind to the same allosteric site and protect rePON1 from OX-LA-induced damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,8 At the same time, on a set of data with a purified recombinant enzyme, iFIT has been shown to compare favorably with Dynafit, the initial velocities approach, and the integrated MM equation without data point removal. 9 Using iFIT at http://www.i-fit.si (last accessed 16. February 2022), any research group that determines MM kinetic parameters from progress curves can solve the problem of unwanted data points at the beginning or end of progress curves.…”
Section: Discussionmentioning
confidence: 99%